2001
DOI: 10.1093/aje/154.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Is Open-Angle Glaucoma Associated with Early Menopause? : The Rotterdam Study

Abstract: The authors examined the association between age at menopause and open-angle glaucoma among women aged > or = 55 years in the population-based Rotterdam Study (1990--1993). Information on age and type of menopause was obtained by interview. Subjects (n = 3,078) were stratified into three categories according to age at menopause: <45 years, 45--49 years, and > or = 50 years, with the last group serving as the reference group. Diagnosis of open-angle glaucoma was based on the presence of a glaucomatous visual fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 29 publications
6
122
2
Order By: Relevance
“…The polymorphism of ERb gene is associated with intraocular pressure (IOP) elevation in female patients with open-angle glaucoma (Mabuchi et al 2010), and polymorphisms of ERb increase its risk in males (de Voogd et al 2008). There is also evidence that early menopause (!45 years) may be associated with a higher risk of glaucoma (Hulsman et al 2001). Later menopause (O54 years) has been associated with a reduced risk of developing open-angle glaucoma (Pasquale et al 2007).…”
Section: Eye Disease and The Retinamentioning
confidence: 99%
“…The polymorphism of ERb gene is associated with intraocular pressure (IOP) elevation in female patients with open-angle glaucoma (Mabuchi et al 2010), and polymorphisms of ERb increase its risk in males (de Voogd et al 2008). There is also evidence that early menopause (!45 years) may be associated with a higher risk of glaucoma (Hulsman et al 2001). Later menopause (O54 years) has been associated with a reduced risk of developing open-angle glaucoma (Pasquale et al 2007).…”
Section: Eye Disease and The Retinamentioning
confidence: 99%
“…In addition, elderly females on HRT have shown reduced prevalence of nuclear cataract [26, 27], glaucoma [28]and age-related macular degeneration [29]. There is preliminary evidence that early menopause may be associated with increased risk for several major ocular diseases, including glaucoma, which may be linked to ocular ischemia [30, 31]. In previous studies the effects of menopause and HRT on retrobulbar blood flow were not well defined [32, 33, 34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…(19) In our study, IOP increased in women as the number of years after they attained menopause-increased. Although direct effect about number of years after attaining menopause is not shown in earlier studies, studies show that there was an increased risk of open angle glaucoma in women who experienced an early natural menopause (20) A less than 10% decline in blood pressure during the night is known as a non-dipping blood pressure (BP) pattern. The study found that Non-dippers were older (P=0.04), postmenopausal (P=0.003) and had lower stress scores (P=0.02) than their dipper counterparts.…”
Section: Discussionmentioning
confidence: 99%